2004
DOI: 10.1002/pssb.200402044
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of layered semiconductor GaS doped with Mn

Abstract: PACS 71.55. Ht, 78.55.Hx Manganese (Mn)-doped GaS single crystals were grown by the Bridgman technique. Radiative recombination mechanisms have been investigated using photoluminescence (PL) measurement. The PL spectrum (at 77 K) related to the impurity level is dominated by the new emission band at 2.002 eV. The temperature dependences of the PL intensity, peak energy, and full width at half-maximum are characterized by the recombination mechanism of the configurational coordinate model. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Significant emission extends in a tail to longer wavelengths. Comparing with reported absorption measurements that give an indirect bandgap of GaS of 2.53 eV ( T = 300 K) , and 2.5–2.6 eV ( T = 77 K), as well as our EELS results showing E g = 2.65 eV for (few nm) thin single type (i) nanowires (Figure ), we can assign the strong CL emission at ∼2.58 eV to band-edge luminescence. The linescan of Figure (c) shows other notable features.…”
Section: Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Significant emission extends in a tail to longer wavelengths. Comparing with reported absorption measurements that give an indirect bandgap of GaS of 2.53 eV ( T = 300 K) , and 2.5–2.6 eV ( T = 77 K), as well as our EELS results showing E g = 2.65 eV for (few nm) thin single type (i) nanowires (Figure ), we can assign the strong CL emission at ∼2.58 eV to band-edge luminescence. The linescan of Figure (c) shows other notable features.…”
Section: Results and Discussionsupporting
confidence: 87%
“…Single nanowire absorption measurements by EELS (Figure 6(a−c)) show a characteristic energy loss onsetassociated with interband transitions across the fundamental bandgapat E g = 2.65 eV, close to the previously reported bandgap of GaS. 37,38 Features between 3 and 10 eV are likely associated with special points in the GaS dielectric function seen previously, 39,40 while the peak at ∼17 eV has been explained by an excitation of the GaS bulk plasmon. 8,41 At low energy (in the gap region), the spectra show structure with intensity above the noise level whose energy coincides with emission features observed in CL (see below), i.e., which may be associated with losses due to transitions between gap states.…”
Section: Resultssupporting
confidence: 86%
“…It is well known that impurity states play an important role in the semiconducting optoelectronic devices. [17][18][19][20][21] Based on previous studies, Mg doping in a semiconductor is common in particular for GaN-based semiconductors to achieve p-type conductivity. 22,23 Moreover, the capability of achieving p-type doping in a GaN semiconductor has led to rapid development of the III-Nitride semiconductor light-emitting diodes (LED) technology by improving the internal quantum efficiency 24,25 and current injection efficiency in LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of indirect band gap energy E g of GaS as a function of temperature is also indicated for comparison in the figure. We evaluated E g from the bound exciton peak energy [12]. The values of 14 meV for binding energy and 10 meV for phonon energy were used in the calculation [5].…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the deep recombination levels due to Cu atoms are localized at 1.23 and 1.48 eV below the conduction band. The 2.002 eV emission band was observed in the PL spectrum of Mn-doped pGaS [12]. This emission band is related to the acceptor-vacancy complex center and is caused by the recombination mechanism of the CC model.…”
Section: Introductionmentioning
confidence: 93%